scCODA is a Bayesian model for compositional single-cell data analysis - M. Büttner (Nature Portfolio, 2021)
Imbalance and loss of cell types is a hallmark in many diseases. Still, quantifying compositional changes in scRNAseq data remains challenging. Here the authors present scCODA, a Bayesian model to assess cell type compositions in scRNA-seq data.